They Shoot, They Score: The New Rules of Marketability Madness - Marrone Echeverria,Valeria Isabel; Casi Josefsson,Josef (2025)
This study aims to quantitatively examine the impact of on-court, off-court, and university-related factors on athlete marketability. It further investigates whether gender moderates these relationships. A quantitative approach was chosen, utilizing secondary data collected from collegiate basketball athletes’ social media profiles and university rosters for the 2024-2025 season. Generalized Linear Model analyzed the relationships and tested the moderation between variables. This study draws on secondary data collected from publicly available Instagram profiles of Division I basketball athletes and official performance statistics from academic institutions. A supplementary interview with a former Division I athlete and current sports agent was also conducted to enhance the interpretation of the quantitative results. The research has contributed by integrating Source Credibility Theory and Social Identity Theory to analyze how different factors jointly influence athlete marketability. Athletes should take into account leveraging social media features, maintaining brand consistency, and building strong team identities to strategically manage both their digital presence and athletic performance to maximize marketability. This study concludes that athlete marketability is strongly impacted by off-court factors. The research provides a deeper understanding of how athletes can strategically enhance their personal brands in the evolving sports marketing landscape.
Keywords: Athlete Marketability; NIL; Sports Marketing; Personal Branding; Source Credibility Theory; Social Identity Theory